Association Between Degree of Gastritis and Malondialdehyde Level of Gastritis Patients at Adam Malik General Hospital Medan - Darmadi Darmadi; Gontar Alamsyah Siregar; Leonardo Basa Dairi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Background: The main pathogenesis of gastritis is inflammation which process can not be separated from the role of free radicals. Malondialdehyde (MDA) is a free radical biomarker and which increases in gastritis patients. However, studies on MDA were generally performed on experimental animals or examined MDA in gastric mucosa. The aim of this study is to determine the association of histopathological degrees of gastritis (the degree of lymphocyte infiltration, neutrophil activity, atrophy, and intestinal metaplasia) with plasma MDA level.Method: Cross-sectional study of 40 consecutive gastritis patients who came to endoscopic unit of Adam Malik General Hospital Medan, from January to May 2017. Assessment for the severity of chronic inflammation, neutrophil activity, atrophy, and intestinal metaplasia refers to Updated Sydney System. Plasma MDA levels were examined using an HPLC MDA kit. Univariate and bivariate (Chi-square and fisher exact test) analysis were performed with SPSS version 22.Results: A total of 26 patients (65%) were men with an average age of 49.25 years. Lymphocyte infiltration was observed in 100% of specimens, neutrophil infiltration in 37.5%, atrophy in 22.5%, and intestinal metaplasia in 22.5%. There was a significant association between degree of lymphocyte infiltration with MDA level (p = 0.014; PR = 8.667; 95% CI: 1.52-89.52). There was a significant association between degree of neutrophil activity with high MDA level (p = 0.002; PR = 11.33; 95% CI: 2.64-48.74). There was a significant association between degree of atrophy with high level of MDA (p 0.001; PR = 14; 95% CI: 3.4–57.648). There was a significant association between degree of intestinal metaplasia with high MDA level (p = 0.001; PR = 12.5; 95% CI: 3.76-24).Conclusion: There were significant associations between degree of lymphocyte infiltration, neutrophil activity, atrophy, and intestinal metaplasia with high level of MDA.